Executive Committee Minutes 2018-08-23 - Academic Senate:::::::::
Agenda Approved. Minutes of 5/10/18 Approved. Chair Report. President Report. Provost Report. Vice President of Administration and Finance Report. Minimal adjustments to Music BA/BM – Approved for Senate consent calendar. Schedule Gordon McDougall to visit Senate. Catering at the Senate. APARC Report. EPC Report. FSAC Report. SAC Report. Discussion of how faculty governance intersects with administrative initiatives across campus such as Stevenson Remodel and move out plan, streamline modules, space utilization generally, strategic planning, relationship of SEIE to the other Schools. CFA Report. Associated Students Report. Senate Agenda approved.